Alignment under Magnetic Field of Mixed Fe2O3/SiO2 Colloidal Mesoporous Particles Induced by Shape Anisotropy. Issue 43 (14th September 2016) - Li, Jheng‐Guang; Fornasieri, Giulia; Bleuzen, Anne; Gich, Martí; Gloter, Alexandre; Bouquet, Frédéric; Impéror‐Clerc, Marianne
Abstract : When using the bottom‐up approach with anisotropic building‐blocks, an important goal is to find simple methods to elaborate nanocomposite materials with a truly macroscopic anisotropy. Here, micrometer size colloidal mesoporous particles with a highly anisotropic rod‐like shape (aspect ratio ≈ 10) have been fabricated from silica (SiO2 ) and iron oxide (Fe2 O3 ). When dispersed in a solvent, these particles can be easily oriented using a magnetic field (≈200 mT). A macroscopic orientation of the particles is achieved, with their long axis parallel to the field, due to the shape anisotropy of the magnetic component of the particles. The iron oxide nanocrystals are confined inside the porosity and they form columns in the nanochannels. Two different polymorphs of Fe2 O3 iron oxide have been stabilized, the superparamagnetic γ‐phase and the rarest multiferroic ε‐phase. The phase transformation between these two polymorphs occurs around 900 °C. Because growth occurs under confinement, a preferred crystallographic orientation of iron oxide is obtained, and structural relationships between the two polymorphs are revealed. These findings open completely new possibilities for the design of macroscopically oriented mesoporous nanocomposites, using such strongly anisotropic Fe2 O3 /silica particles. Moreover, in the case of the ε‐phase, nanocomposites with original anisotropic magnetic properties are in view. Abstract : Fe2 O3 /SiO2 colloidal mesoporous particles with high shape anisotropy are promising building blocks to achieve macroscopically oriented nanocomposites. When dispersed in a solvent, these particles can be easily oriented under magnetic field. Two polymorphs of iron oxide can be stabilized, the superparamagnetic γ phase and the rarest multiferroic ε phase, opening new perspectives for nanocomposites with anisotropic magnetic properties.